Comparative Transcriptomics Highlights New Features of the Iron Starvation Response in the Human Pathogen Candida glabrata - Benchouaia, Médine; Ripoche, Hugues; Sissoko, Mariam; Thiébaut, Antonin; Merhej, Jawad; Delaveau, Thierry; Fasseu, Laure; Benaissa, Sabrina; Lorieux, Geneviève; Jourdren, Laurent; Le Crom, Stéphane; Lelandais, Gaëlle; et al. (Frontiers in Microbiology, 2018)
In this work, we used comparative transcriptomics to identify regulatory outliers (ROs) in the human pathogen Candida glabrata. ROs are genes that have very different expression patterns compared to their orthologues in other species. From comparative transcriptome analyses of the response of 8 yeast species to toxic doses of selenite, a pleiotropic stress inducer, we identified 38 ROs in C. glabrata. Using transcriptome analyses of C. glabrata response to 5 different stresses, we pointed out 5 ROs which were more particularly responsive to iron starvation, a process which is very important for C. glabrata virulence. Global chromatin Immunoprecipitation and gene profiling analyses showed that 4 of these genes are actually new targets of the iron starvation responsive Aft2 transcription factor in C. glabrata. Two of them (HBS1 and DOM34b) are required for C. glabrata optimal growth in iron limited conditions. In S. cerevisiae, the orthologues of these two genes are involved in ribosome rescue by the NO GO decay (NGD) pathway. Hence, our results suggest a specific contribution of NGD co-factors to the C. glabrata adaptation to iron starvation.